Regioselectivity in the Thermal Rearrangement of Unsymmetrical 4-Methyl-4H-1,2,4-triazoles to 1-Methyl-1H-1,2,4-triazoles - Per H.J. Carlsen; Odd R. Gautun (Molecules, 2001)
The rearrangement of 4-methyl-3,5-diaryl-4H-1,2,4-triazoles to the corresponding 1-methyl-3,5-diaryl-1H-1,2,4-triazoles showed regioselectivity comparable to that observed for the alkylation of 3,5-diaryl-1H-1,2,4-triazoles. This lends support to a proposed mechanism for the rearrangement that involves consecutive nucleophilic displacements steps.